(untitled) (World Bulletin of Education and Learning, 2025)
This article explores the theoretical foundations of traditional Uzbek vocal art, focusing on its modal system, regional schools, pedagogical practices, and expressive techniques. Rooted in the centuries-old maqom tradition, Uzbek vocal performance integrates complex modal structures, rhythmic patterns, and poetic expression. This study analyzes the specific characteristics of Uzbek maqom, the oral transmission system via the master-apprentice relationship, and the regional stylistic variations in performance. Drawing on ethnomusicological research and comparative musicology, this paper aims to present a comprehensive theoretical framework that highlights the unique features of Uzbek traditional singing within the broader context of Central Asian music heritage.